Comparative nutritional analysis of total protein in the muscles of local fish from Libyan waters - Randa Taher El beshti; Ali Abdussayed Ali Ghania; Najat Elkhtroshi; Magda Saleh Elwalid (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to estimate the total protein content in muscle tissue of six marine species commonly found in Libyan waters, Sardinella aurita (Sardine), Sphyraena sphyraena (barracuda), Epinephelus costae (dusky grouper), Pagellus erythrinus (red porgy), Scomber japonicus (chub mackerel), and Oblada melanura (saddled seabream). A total of 18 specimens from each species were collected from fish market at Bab Al-Bahr, Tripoli. Length and Wight measurements were recorded, with average length ranging from 19.22 to 32.35 cm and weights from 60.17 to 190.17 g. Protein content was determined using the Kjeldahl method. The results revealed significant variation in total protein levels among the studied species. The highest protein concentration was observed in the muscle tissue of Pagellus erythrinus, indicating its superior nutritional value. This was followed by Sardinella aurita and Scomber japonicus. In contrast, lower protein levels were recorded in Sphyraena sphyraena and Oblada melanura, with Epinephelus costae exhibiting the lowest protein content among the sampled species.